Evaluasi Program Kegiatan Belajar Mengajar Mata Pelajaran Pendidikan Jasmani Masa Pandemi Covid-19 - Purnama, Yudhi; Rozi, Fatkhur; Usmanto, Usmanto (Universitas Hamzanwadi, 2022)
This study was conducted to find out how the teaching and learning program for physical education subjects at Madrasah Aliyah (MA) throughout Pekalongan City during the corona virus pandemic. The research design uses an evaluative approach using the Context, Input, Process and Product (CIPP) method. Data were collected through interview, observation and research methods with qualitative descriptive analysis. The results show that in general the teaching and learning program for physical subjects in MA in Pekalongan City has been going well with the policies of the government although it has not been fully implemented to its full potential. Context, the material that has been delivered in accordance with the curriculum. Input, teacher qualifications are quite appropriate, infrastructure is quite good but limited and students are not in accordance with the attendance list. The process, KBM is carried out boldly and scheduled face-to-face, with good administration. Product, learning outcomes are in accordance with completeness even though aspects of skills (psychomotor) are still lacking. Teachers need to learn to improve the online learning, assessment and assessment system during the Covid-19 pandemic to further improve student competence.